The Role of Human Resource Management in Improving the Performance of Makassar Regional BPRS Employees - Idrus, Arifin (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to determine the role of Human Resource Management in Improving the Performance of BPRS MAU Makassar Employees from an Islamic Perspective. This research method uses a qualitative approach by describing findings in the field. Data collection techniques in this research are through interviews, observation, and documentation studies. Data analysis uses inductive thinking and benefits in this research as information regarding employee performance development in Sharia banking institutions. The research results of BPRS Partners Agro Business Makassar show that the role of Human Resources Management has been proven to have a significant influence on improving employee performance. This has been proven by the increase in the number of customers from year to year and with the implementation of BPRS Partners Agro Business - Makassar management, namely in the recruitment process. and selection, training, and compensation or rewards given to employees and the application of Islamic values in Human Resource Management.